Social networks and gender dimensions in use of irrigation by farmers in Alamata Woreda, Southern Tigray, Ethiopia - Hailemariam, M. (Haramaya University, 2008)
Access to input / technology, information / knowledge, credit / finance is very decisive for the development of a given society in general and irrigation based high value crop production in particular. The identification of the contribution of social networks in facilitating access to these resources and services and thereby influence crop choice among irrigation user farmers is vital to identify the important actors contributing in irrigation based vegetable production. This study was undertaken in Alamata woreda, Southern Zone, Tigray National Regional State and has been designed to give a clue on the existing formal and informal social networks and groups in facilitating access to resources and services, among irrigation based vegetable growers and non growers. The practical contributions of social networks and their gender implications in facilitating access to inputs / technologies, information / knowledge and credit / finance in irrigation based vegetable production; and identification of alternatives for enhancing the role and sustainability of these social networks for promoting vegetable production in the woreda was the focus of this study. Identifying the factors for choice of crops by farmers in using irrigation was also another additional objective of the study. Multistage sampling procedure was employed to select 4 PAs out of 10PAs in the woreda and 150 sample households from the 4 PAs. Both qualitative and quantitative data were collected to obtain reliable information from primary and secondary sources. Data analysis was done using descriptive statistics, mainly. Chi-square and ranking was used to see the contribution of social networks & their relative importance in facilitating access to resources and services among vegetable growers and non growers as well as FHHs & MHHs, separately. T-test, chi-square test, mean, percentage and frequencies were also used to identify preceding factors for growing or not growing vegetables, in addition to binary logistic regression model. This study revealed variations between vegetable growers and non growers as well as MMHs and FHHs in terms of membership in different economically oriented groups, frequency of use of different social networks as a source of different inputs and services and in terms of perceived relative importance of different social networks (formal and informal networks). The binary logistic regression model out put showed that marital status, education level, on farm income, DA contact, participation in extension events and number of relatives & close friends were found to have positive and significant influence on the choice of vegetable crops by farmers. The study also revealed that formal networks are the most frequently used and the most important sources of inputs and information for vegetable growers in general and MHHs in particular, on the other hand informal networks were found to be the most frequently used and the most important sources of inputs and information for vegetable non growers in general and FHHs in particular. Generally, both informal and formal networks are found to be important in the study area, hence recognizing the importance of informal networks (groups), and strengthening & organizing them in to self help groups is very important. In addition, after identifying influential social networks establishing linkage among formal and informal networks has paramount importance for better efficiency of the contribution of social networks, in enhancing culture of growing vegetable crops among the community members in particular, and rural development in general.